Reading, Writing, and Learning Disorders in Dyslexic Patients in Pematang Siantar city - Hum, Gustianingsih M.; Effendi, Elmeida; Ali, Ali (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This paper is about dyslexia patients who cannot read, write, and speak. Developmental dyslexia is innate and due to genetic or hereditary factors. people with dyslexia will carry this disorder for the rest of their lives and cannot be cured. Not only do they have difficulties at reading, they also experience barriers to spell, write, and some other language aspects. However, dyslexic children have normal or even above average levels of intelligence. With special handling, the obstacles they experience can be minimized and acquired dyslexia occur due to interference or changes in the left brain hemisphere.